Locust bean gum: exploring its potential for biopharmaceutical applications - Dionísio, Marita (2013)
Polysaccharides have been finding, in the last decades, very interesting and useful applications in the biomedical and, specifically, in the biopharmaceutical field. Locust bean gum is a polysaccharide belonging to the group of galactomannans, being extracted from the seeds of the carob tree (Ceratonia siliqua). This polymer displays a number of appealing characteristics for biopharmaceutical applications, among which its high gelling capacity should be highlighted. In this review we describe critical aspects of locust bean gum, contributing for its role in biopharmaceutical applications. Physicochemical properties, as well as strong and affective synergies with other biomaterials are described. The potential for in vivo biodegradation is explored and the specific biopharmaceutical applications are discussed.